Celebrating Christmas based on children’s drawing – comparative study on the example of Poland, Austria and Italy = Świętowanie Bożego Narodzenia na podstawie rysunków dzieci– studium porównawcze na przykładzie Polski, Austrii i Włoch - Sobczyk-Gąsiorek, Anna (Przegla̜d religioznawczy, 2020)
Christmas is one of the most important holidays not only for Christians, but also for people not associated with this religion. For some it is a holy time, referring to the sphere of the sacred, for others a period of family or group meetings, for others simply a time of winter rest. However, it is experienced in the context of events and signs whose origin is Christian. Today, these signs and events are given different meanings, often different from the culture from which they originated. This article is about the specifics of celebrating Christmas in Poland, Austria and Italy, based on children’s drawings. When analyzing visual performances, the area of the image itself was adopted, i.e. the content and form of drawings of children at a younger school age. In particular, an attempt was made to diagnose dominant symbols related to the celebration of Christmas in Polish, Austrian and Italian families.